Evaluation of agro-industrial wastes, their state and mixing ratio for maximum polygalacturonase and biomass production in submerged fermentation - Göğüş, Nihan (2015)
The potential of important agro-industrial wastes, apple pomace (AP) and orange peel (OP) as C sources, was investigated in the maximization of polygalacturonase (PG), an industrially significant enzyme, using an industrially important microorganism Aspergillus sojae. Factors such as various hydrolysis forms of the C sources (hydrolysed-AP, non-hydrolysed-AP, hydrolysed-AP + OP, non-hydrolysed-AP + OP) and N sources (ammonium sulphate and urea), and incubation time (4, 6, and 8 days) were screened. It was observed that maximum PG activity was achieved at a combination of non-hydrolysed-AP + OP and ammonium sulphate with eight days of incubation. For the pre-optimization study, ammonium sulphate concentration and the mixing ratios of AP + OP at different total C concentrations (9, 15, 21 g l−1) were evaluated. The optimum conditions for the maximum PG production (144.96 U ml−1) was found as 21 g l−1 total carbohydrate concentration totally coming from OP at 15 g l−1 ammonium sulphate concentration. On the other hand, 3:1 mixing ratio of OP + AP at 11.50 g l−1 ammonium sulphate concentration also resulted in a considerable PG activity (115.73 U ml−1). These results demonstrated that AP can be evaluated as an additional C source to OP for PG production, which in turn both can be alternative solutions for the elimination of the waste accumulation in the food industry with economical returns.